How do you simplify 5xy - 6x^2y^2 + 4x^2y^2 - 2xy?

2 Answers
Jun 13, 2017

See a solution process below:

Explanation:

First, group and combine like terms:

5xy - 6x^2y^2 + 4x^2y^2 - 2xy =>

-6x^2y^2 + 4x^2y^2 + 5xy - 2xy =>

(-6 + 4)x^2y^2 + (5 - 2)xy =>

-2x^2y^2 + 3xy

Now, factor an xy out of each term:

(xy * -2xy) + (3 * xy) =>

xy(-2xy + 3)

Jun 13, 2017

-xy(2xy-3)

Explanation:

You would collect equal variables together

(5xy - 2xy)+(-6x^2y^2 + 4x^2y^2)

Simplify it

5xy - 2xy = 3xy
-6x^2y^2 + 4x^2y^2 = -2x^2y^2

3xy -2x^2y^2

Factorise it by taking a common factor which is -xy

-xy(2xy-3)